Accurate reliability evaluation using quantum‐dot cellular automata probabilistic transfer matrix. (1st February 2014) - Chen, Xiangye; Cai, Li; Jia, Kaixiang; Wang, Zhichun; Cui, Huanqing
Abstract : The probabilistic transfer matrix (PTM) plays an important role in analysing the transient faults and the reliability of digital logic circuits. Proposed a modified PTM (QPTM) for quantum‐dot cellular automata (QCA). It has two features different from the previous PTM model: (i) finding more accurate matrices for the wires; and (ii) dividing the QCA circuits more reasonably. Simultaneously, the wire's correct probability is curved by a Gaussian function to enable it to emerge successfully. By using this QPTM, the detailed and extensive simulation results gained reveal that the reliabilities obtained from the PTM analysis of the same circuit could differ at 9%. As for the reliabilities achieved from the PTM and the QPTM, the difference rises to 30%. The simulations obtained have proved that the PTM has weaknesses when presenting the effects of the wire's length and division on the circuit reliabilities.